2017
DOI: 10.14253/acn.2017.19.1.3
|View full text |Cite
|
Sign up to set email alerts
|

Sensory and motor axons are different: implications for neurological disease

Abstract: Axons are required to maintain specific discharge rates and patterns, and as a consequence, the ability to conduct an impulse with minimal expenditure of energy will create different needs for different axonal populations. There may be only one role for an axon, and that is to conduct an impulse securely from one end to the other, but it is to be expected that the biophysical properties of sensory and motor axons may differ in order for them to fulfil this role. Specifically, motor axons that innervate muscle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 32 publications
(35 reference statements)
0
2
0
Order By: Relevance
“…The multivariate analysis confirmed that the reduction in the sensory response in the sural nerve (longest sensory nerve) is positively correlated with a reduction in HRV in Valsalva and HRV DB, which suggests a concomitant involvement of sensory-somatic and parasympathetic nerve fibres in T2DM. The differences between biophysical properties (excitability) and in ion channel functions between motor and sensory axons can subject the sensory fibres to greater metabolic disturbances; therefore, in early DN stages, the sensory axons from the peripheral nerves are initially affected [32].…”
Section: Discussionmentioning
confidence: 99%
“…The multivariate analysis confirmed that the reduction in the sensory response in the sural nerve (longest sensory nerve) is positively correlated with a reduction in HRV in Valsalva and HRV DB, which suggests a concomitant involvement of sensory-somatic and parasympathetic nerve fibres in T2DM. The differences between biophysical properties (excitability) and in ion channel functions between motor and sensory axons can subject the sensory fibres to greater metabolic disturbances; therefore, in early DN stages, the sensory axons from the peripheral nerves are initially affected [32].…”
Section: Discussionmentioning
confidence: 99%
“…Automated nerve excitability testing (ANET) using a threshold tracking protocol is a novel technique used in neurophysiology to assess the axonal excitability within peripheral nerves in vivo . 1–3 The results of ANET reflect the biophysics of the relevant voltage-gated ion channels and resultant membrane potentials of peripheral nerves. 4–6 This technique has contributed to improving the understanding of the pathophysiology of peripheral neuropathies and motor neuron disease.…”
mentioning
confidence: 96%